2016
DOI: 10.1007/s10067-016-3424-5
|View full text |Cite
|
Sign up to set email alerts
|

The usage of biological DMARDs and clinical remission of rheumatoid arthritis in China: a real-world large scale study

Abstract: The aims of this study are to characterize the biological disease-modifying antirheumatic drug (bDMARD) usage patterns in real-life and examine the remission rate of rheumatoid arthritis (RA) patients receiving bDMARDs in routine clinical practice in China. Consenting RA patients (≥18 years) from 15 teaching hospitals and receiving marketed bDMARDs were included. In total, 802 patients (81.3 % women, 49.0 ± 13.9 years) were included; 89.5 % were receiving a combination of bDMARDs and conventional synthetic DMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…43 Currently, six bDMARDs are approved for RA treatment in China, and a recent large-scale, real-world study of RA patients in China reported bDMARD usage in routine clinical practice in accordance with treatment guidelines. 48 Interestingly, this study also reported that a lower proportion of patients (10.5%) were prescribed bDMARD monotherapy in China than in the USA (30%), 49 which suggests better compliance with international treatment guidelines that recommend bDMARDs in combination with csDMARDs, rather than as monotherapy. 50 A number of limitations of the current analysis are acknowledged.…”
mentioning
confidence: 77%
“…43 Currently, six bDMARDs are approved for RA treatment in China, and a recent large-scale, real-world study of RA patients in China reported bDMARD usage in routine clinical practice in accordance with treatment guidelines. 48 Interestingly, this study also reported that a lower proportion of patients (10.5%) were prescribed bDMARD monotherapy in China than in the USA (30%), 49 which suggests better compliance with international treatment guidelines that recommend bDMARDs in combination with csDMARDs, rather than as monotherapy. 50 A number of limitations of the current analysis are acknowledged.…”
mentioning
confidence: 77%
“…Some ‘real world’ studies have reported better outcomes than these meta‐analyses, with remission rates or remission/low disease activity (as defined by DAS28 score) as high as 44–63% 18,19 . In the British Society for Rheumatology (BSR) Biologics Registry for Rheumatoid Arthritis, remission (DAS28 <2.6) was achieved in about 15% and low disease activity (DAS28 2.6 to 3.2) in about 26% of patients treated with anti‐TNF therapy between 2001 and 2013 20 .…”
Section: Range Of Biological Therapies For Rheumatoid Arthritismentioning
confidence: 97%
“…Two intended copies of etanercept are available in China: Qiangke and Yi Sai Pu . A study evaluated real‐world use of biologics for RA at 15 teaching hospitals in China and found that etanercept was used by 66.6% of patients . The breakdown of etanercept agents was Yi Sai Pu (58.1%), Enbrel (6.1%) and Qiangke (2.4%) .…”
Section: Approved Anti‐tnf Biosimilars or Intended Copies In Asia Pacmentioning
confidence: 99%
“…A study evaluated real‐world use of biologics for RA at 15 teaching hospitals in China and found that etanercept was used by 66.6% of patients . The breakdown of etanercept agents was Yi Sai Pu (58.1%), Enbrel (6.1%) and Qiangke (2.4%) . The other biologics in use were tocilizumab (17.0%), adalimumab (7.5%) and infliximab (6.6%) …”
Section: Approved Anti‐tnf Biosimilars or Intended Copies In Asia Pacmentioning
confidence: 99%
See 1 more Smart Citation